Determination of optimum values of descriptors to set filters for synthetic tri-pyrrole derivatives (prodiginines) against multi drug resistant strain of plasmodium falciparum - Masand, Vijay H.; Mahajan, Devidas T.; Pourbasheer, Eslam; Hadda, Taibi Ben; Chauhan, Harsh; Gajbhiye, Jayant M.; Alafeefy, A. M. (Current Research in Drug Discovery, 2014)
Abstract: In the present study, we have carried out extensive non-linear Quantitative-Structure Activity Relationship (QSAR) analysis to correlate in vitro anti-malarial activity against multi drug resistant strain of Plasmodium falciparum. Forty-three synthetic prodiginines with different structural features were used for their potential antimalarial activity. Linear, bilinear, biexponential and parabolic equations were developed. These equations were compared to determine the optimum values of descriptors for very useful and easily interpretable descriptors. The optimum values of these descriptors could be helpful in finding and optimizing a good lead compound. Obtained correlations reveal that various factors like lipophilicity, molecular weight and number of bonds have non-linear relation with the anti-malarial activity. Keywords: Prodiginines, Anti-Malarial Activity, Optimum/Desirability Values, Hybrid Inverse-QSAR

Advances and recent applications in LC-MS and HPLC - Azharuddin, Quazi Syed; Mahajan, Devidas T.; Masand, Vijay H.; Alafeefy, Ahmed M.; Gajbhiye, Jayant M.; El-Sayed, Nahed Nasser Eid; Wajid, Abdul; Mohammad, Noor (Elsevier, 2015)
Advances and Recent Applications in LC-MS and HPLC presents the most recent developments in liquid chromatography and mass spectrometry techniques. The book’s content reaches across a range of disciplines and cites several case studies to effectively capture the advanced applications that make LC-MS and HPLC multifunctional and exacting techniques. Liquid chromatography and mass spectrometry systems generate chromatograms of column peaks and can provide molecular weights of separated materials and their solvent complexes. However, while these systems can provide structural information to confirm the identity of the compounds separated, the process is very expensive. This book provides identification of simple compounds resulting from fragmentation studies and their subsequent results, offering the reader access to information unavailable elsewhere and allowing researchers to avoid incurring the costs associated with obtaining the hands-on results that LC-MS systems generate. Applicable to chemical analysis, bioanalysis, and medicinal chemistry, as well as pharmaceutical science, synthetic chemistry, and industrial chemistry, Advances and Recent Applications in LC-MS and HPLC is a multidisciplinary reference that arms scientists with the latest research. Detailed case studies enable researchers to make the book's concepts immediately implementable.

Analysis of pantaprazole na monohydrate and sesquihydrate by powder x-ray diffraction (PXRD) - Mahajan, Devidas T.; Mohmad, Noor; Raut, D. M.; Gajbhiye, Jayant M. (Journal of Medicinal Chemistry and Drug Discovery, 2015)
Pantaprazole Na monohydrate and sesquihydrate were characterized by PXRD.significant difference in the diffraction patterns of Pantaprazole Na hydrates. The sesquihydrate contains all the diffraction peaks of monohydrate in addition to peaks.